The role of phytoplankton composition and microbial community metabolism in sea–air ΔpCO2 variation in the Weddell Sea - Moreau, Sebastien (2013)
The Weddell Sea is known to be a CO2 sink due to active biological and physical pumps. Here we study the relationships of phytoplankton biomass and composition and microbial community metabolism, estimated from simulated in situ incubations and from nutrient′s difference between surface and subsurface waters, with ΔpCO2 in the Weddell Sea, during four austral summers (2002?2005). The ΔpCO2 was significantly negative throughout the Weddell Sea in 2002 (-17.2 ± 28.1 μatm), 2003 (-64.1 ± 31.3 μatm), 2004 (-54.9 ± 61.8 μatm) and 2005 (-63.8 ± 60 μatm), indicating that the Weddell Sea acted as an atmospheric CO2 sink during those summers. The ΔpCO2 was significantly lower in the south than in the center or north of the Weddell Sea. This was consistent with the significantly higher Chlorophyll-a concentrations (Chl-a) observed in the south (2.3 ± 1.9 μg l-1) than in the center (1.3 ± 1.2 μg l-1) or north (1.4 ± 1.7 μg l-1). In contrast, waters were mainly undersaturated in O2, due to the upwelling of oxygen poor Warm Deep Water (WDW). The negative relationship between the ΔpCO2 and the %O2 saturation suggested that planktonic metabolic activities played a role in these gases dynamics, along with the upwelling of WDW. However, these relationships could not be observed from the results of the incubation experiments, probably because of different temporal scales between gas exchanges in incubation experiments and in situ CO2 and O2 dynamics. The dynamics of CO2 and O2 were solely related to the net community production (NCP) and to the gross primary production (GPP) when only stations with Chl-a 41 μg l-1 were considered. A significant relationship was, however, found between ΔpCO2 and the primary production until the time of sampling for all stations when estimated from nutrients depletion between surface and subsurface waters. Finally, the distribution of CO2 and O2 were related to the biomass of diatoms and, contrarily to other seas, to the biomass of phytoflagellates.